2002
DOI: 10.1159/000063656
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Primary Cornea guttata and Morphology of Corneal Endothelium in Aging Japanese and Singaporean Subjects

Abstract: The purpose of the present study was to examine, in the aging people, racial and gender differences in the morphology of corneal endothelium as well as the incidence of cornea guttata in two Asian subject groups, one in Singapore and the other in Japan. Four hundred and sixty-five Chinese Singaporeans and 299 Japanese subjects (residents of Monzen-machi, Ishikawa Prefecture) aged 50 years and older were recruited for the study. Corneal endothelial abnormalities were diagnosed with slit-lamp biomicroscopy and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 11 publications
4
40
3
1
Order By: Relevance
“…6 In our study, there was no sex-related difference in the incidence of cornea pseudoguttata. On the contrary, the ratio of female patients with cornea pseudoguttata (55%) was lower than that of the study population (64.4%).…”
Section: Discussioncontrasting
confidence: 46%
“…6 In our study, there was no sex-related difference in the incidence of cornea pseudoguttata. On the contrary, the ratio of female patients with cornea pseudoguttata (55%) was lower than that of the study population (64.4%).…”
Section: Discussioncontrasting
confidence: 46%
“…Previous studies suggest a prevalence in the United States of approximately 4 to 7%, 22, 23 in Europe of 4.5 to 9%, 15 and in Asia of 3.8 to 8.5%. 16, 17, 24 Although the variation among studies in methods and thresholds utilized to define affectation, such as specular microscopy or slit-lamp examination, limits direct comparison, the data suggest an increased prevalence on the island. This finding is supported by the high frequency of the TCF4 variant allele noted in this isolated population.…”
Section: Discussionmentioning
confidence: 99%
“…FECD demonstrates a female preponderance with a 3.5:1 bias in patients that underwent penetrating keratoplasty for FECD at Duke University Eye Centre, USA (Afshari et al, 2006). Prevalences of 11% females vs 7% males in Icelanders, 8.5% vs 4.4% in Chinese Singaporeans, and 5.5% vs 1.5% in Japanese were also found (Kitagawa et al, 2002;Zoega et al, 2006). An association with hypermetropia is common (Pitts and Jay, 1990).…”
Section: Introductionmentioning
confidence: 92%
“…The Reykjavik Eye Study revealed a 9.2% prevalence in residents over 55 years old in Reykjavik, Iceland (Zoega et al, 2006); a study found a prevalence of 6.7% in an over-50 year old Chinese Singaporean population and 3.7% in an over-50 year old Japanese population (Kitagawa et al, 2002). It typically presents in the sixth decade but early onset cases have also been reported (Borboli and Colby, 2002).…”
Section: Introductionmentioning
confidence: 99%